Analysis of Brain Wave Activity Realtime Using NeuroSky Sensors With LabVIEW - Destra Andika Pratama; Masayu Anisah; Richi Agung Pratama (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
The brain is the part of the body that gives us the ability to live, react to all external stimuli, and coordinate our entire body. The human brain constantly generates electrical impulses. These electric currents are often referred to as brain waves. EEG (electroencephalography) is a bioelectrical measurement used in the biomedical field to study the human brain. Through this research, a sensor system will be developed that can detect brain waves non-invasively and transmit signals wirelessly via a Bluetooth connection. The detected EEG signal will be displayed in graphical form using signal parameters. To obtain brain wave signals, sensor electrodes are placed directly on reference points on the surface of the scalp in the front and left ears. The captured brainwave signal will be wirelessly transmitted via USB Bluetooth BLE 4.0. Next, the brainwave signal data will be converted and processed via USB Bluetooth BLE 4.0, which is connected to the USB port on the laptop. Then, the brain wave signal will be displayed in graphical form in real-time and analyzed using LabVIEW software. The results of this study indicate that the monitoring system that works on LabVIEW can display real-time data from the NeuroSky sensor wirelessly, and the type of brain waves and the frequency of the resulting brain waves can vary depending on the condition of the brain at the time